Pengaruh Struktur Modal, Kebijakan Dividen dan Kebijakan Hutang Terhadap Nilai Perusahaan (Studi empiris pada perusahaan pertambangan yang terdaftar di BEI tahun 2020-2022) - Siti Aisyah; Alfiati Silfi; Eka Hariyani (Pelantar Press, 2024)
The aim of this research is to determine and analyze the influence of dividend policy, debt policy and profitability on company value in mining depositors listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. This research was conducted on 18 companies listed as mining companies on the Stock Exchange The effect of Indonesia during the 2020-2022 period is used as the population. By using a sampling technique, namely purposive sampling, we obtained 4 issuers who met the criteria in this research. The research methodology used is a qualitative descriptive analysis method and a quantitative descriptive analysis method. The analysis method used uses multiple linear regression. The results of this research can be concluded that simultaneously there is a significant influence from the independent variables, namely Dividend Policy (DPR), Policy Debt (DAR) and Capital Structure (DER) on the dependent variable, namely Company Value (PBV).Â Â